Optical waveguide based surface profiling apparatus - EARTHROWL-GOULD, TIMOTHY E; BENNION, IAN; ALLSOP, THOMAS D.P (2006)
Surface profiling apparatus 10 according to one embodiment comprises three long period gratings (LPGs) 12, 14, 16 fabricated in progressive three layered (PTL) fibre 18 and embedded within a deformable carrier member 40 comprising a skeleton 42 provided between two sheets of flexible rubber skin 44, 46. The LPGs 12, 14, 16 are illuminated by three wavelength modulated, narrow bandwidth optical signals, each having a different wavelength and modulation frequency. A photodetector 26 connected to three lock-in amplifiers 28, 30, 32 measures the amplitudes of the first and second harmonic frequency components of the photodetector output signal corresponding to each LPG 12, 14, 16. Similar surface profiling apparatus 10 forms the basis for respiratory function monitoring apparatus 100 in which five LPGs are provided within each of four PTL fibres 104, 106, 108, 110, and embedded in four carrier members 40a-d attached to a garment 114 to be worn by a subject.